Two Suturing Techniques for the Prevention and Treatment of Nasal Valve Collapse After Mohs Micrographic Surgery. Issue 3 (March 2017) - Miladi, Anis; McGowan, Joseph W.; Donnelly, Heidi B.
Abstract : BACKGROUND: Tumor extirpation of nonmelanoma skin cancer (NMSC) adjacent to the alar groove, using Mohs micrographic surgery (MMS), may risk causing internal nasal valve (INV) collapse, resulting in reduced airflow during inspiration. There are many surgical options described in the literature to repair INV collapse as a postoperative corrective procedure, but few exist as an intra-operative preventative procedure. OBJECTIVE: The authors present 2 distinct methods to prevent and treat INV collapse during the repair of a perialar surgical defect caused by MMS. METHODS: A 3-point stitch method or a modified suspension suture technique was used to prevent INV collapse during the repair of MMS defects overlying the alar groove, for nonmelanoma skin cancers. The 3-point stitch was used with a complex repair. The modified suspension suture was used with flap reconstruction. RESULTS: The 3-point stitch and the modified suspension suture are simple, single-stage surgical solutions for perialar defects with collapse of the INV caused by loss of subcutaneous tissue during MMS. Once executed, patients experienced immediate subjective airflow improvement which was also supported by clinical examination. Patients were followed at 1 week and at 3 months postoperatively. Thirty-four of 35 patients reported good functional and cosmetic results and were satisfied with the final outcome. CONCLUSION: The 3-point stitch and the modified suspension suture techniques are easy and simple methods that can be incorporated into reconstruction after MMS for defects of variable depth covering any multisubunit perialar region to prevent or correct INV collapse.